1995
DOI: 10.1002/bjs.1800820850
|View full text |Cite
|
Sign up to set email alerts
|

Port site metastases after laparoscopic colorectal surgery for cure of malignancy

Abstract: and the majority of patients have acute ulcers (65 per cent)'. NSAIDs are a common aetiological factor. Although the incidence of H. pylon has been shown to be independent of sex it correlates closely with socioeconomic class, with an increased incidence in the lower socioeconomic groups'. This fact may account for the high proportion of patients infected with H. pylon in this study. In their study from Glasgow, Reinbach et aL3 found that only 47 per cent of patients presenting with acute perforated duodenal u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 2 publications
0
33
0
Order By: Relevance
“…Prior reports suggested that high and/or pulsatile pneumoperitoneum, especially in lengthy procedures, may enhance migration tumor cells from the venous plexus of the bladder (whose pedicles are squeezed throughout the procedure) and contribute to early tumor recurrence 8,28,29 31 . However, the lymph node yield in the same study was the same for either approach and the differences reported were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Prior reports suggested that high and/or pulsatile pneumoperitoneum, especially in lengthy procedures, may enhance migration tumor cells from the venous plexus of the bladder (whose pedicles are squeezed throughout the procedure) and contribute to early tumor recurrence 8,28,29 31 . However, the lymph node yield in the same study was the same for either approach and the differences reported were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The localized inflammation from the trauma induced by the cannula and trocar insertion increases the potential for a tumor cell to implant. This phenomenon was first suggested in 1995 in a letter to the British Journal of Surgery [63]. This phenomenon was further elucidated the following year in a study that suggested that the presence of a pneumoperitoneum creates a pressure gradient with a subsequent outflow of gas and floating tumor cells through the port wounds, creating a chimney effect that does not occur in a standard wound [64].…”
Section: The Chimney Effectmentioning
confidence: 92%
“…17 Tumor cells implant more easily and successfully during early wound healing, adhering to fibrin deposited at the site of surgical wound as a part of normal healing. 18 The presence of growth factors at the wound site promotes the survival and propagation of these cancer cells. As suggested by few animal studies, the port-site incision is more conducive than the laparotomy incision for tumor seeding.…”
Section: Discussionmentioning
confidence: 99%